An as-yet-unpublished map of Belgrade from the beginning of the 18th century - Dulović Vladimir (Nasleđe)
Little-known to the professional public, the map of Belgrade from the National Library in Paris with the signature Ge C 10281 brings new information about the appearance of the city, and in particular its residential quarters, at the beginning of the 18th century. By comparing it with other maps and plans from that period, we arrive at the conclusion that it was created between 1719 and the early months of 1721, and that it was made as part of preparations for the construction of town fortifications according to the plans of Major Francois Nicolas Suly. Through a thorough analysis and cross-referencing of data from the corpus of knowledge about Belgrade at that time, we obtained valuable information about several key buildings, about its market areas (čaršija), and about the development of a number of districts. Thus, this map of the city has proved to be one of the most valuable from the era before the baroque reconstruction.